A systematic review of trustworthy and explainable artificial intelligence in healthcare: assessment of quality, bias risk, and data fusion - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
A systematic review of trustworthy and explainable artificial intelligence in healthcare: assessment of quality, bias risk, and data fusion by Alamoodi, Abdullah Hussein